Literatures of the world : beyond world literature - Ette, Ottmar (Brill, 2021)
"Beginning with Erich Auerbach's reflections on the Goethean concept of world literature, Ottmar Ette unfolds the theory and practice of Literatures of the World. Today, only those literary theories which are oriented upon a history of movement are still capable of doing justice to the confusing diversity of highly dynamic, worldwide transformations. This is because they examine transareal pathways in the field of literature. This volume captures literary processes of exchange and transformation between the Mediterranean, Atlantic and Pacific as well as the interplay of different ways of narrating space and time. Thus, this volume speaks from a fractal point of view and unfolds multiple perspectives. Literatures of the World allow the reader to think in different logical frameworks at the same time, therefore shaping our future on the basis of the diversity of humankind"